Case-fatality and temporal trends in patients with psoriasis and end-stage renal disease - Wild, Johannes; Keller, Karsten; Karbach, Susanne; Weinmann-Menke, Julia; Münzel, Thomas; Hobohm, Lukas (Journal of Clinical Medicine, 2022)
Background and Objectives: During the last decades, growing evidence corroborates that chronic inflammatory disease impairs the body beyond the cutaneous barrier. Linkage between psoriasis and kidney disease, and in particular between psoriasis and end-stage renal disease (ESRD), have not yet been elucidated. We sought to analyze the impact of concomitant psoriasis on the in-hospital outcomes of patients hospitalized with ESRD. Patients and Methods: We analyzed data on characteristics, comorbidities, and in-hospital outcomes of all hospitalized patients with ESRD stratified for concomitant psoriasis in the German nationwide in-patient sample between 2010 and 2020. Results: Overall, 360,980 hospitalizations of patients treated for ESRD in German hospitals were identified from 2010 to 2020 and among these 1063 patients (0.3%) additionally suffered from psoriasis. While the annual number of all ESRD patients increased within this time, the number of patients with ESRD and the additional psoriasis diagnosis decreased slightly. Patients with ESRD and psoriasis were five years younger (66 [IQR, 56-75] vs. 71 [59-79] years, p < 0.001), were more often obese (17.5% vs. 8.2%, p < 0.001) and more frequently had cancer (4.9% vs. 3.3%, p < 0.001), diabetes mellitus (42.7% vs. 38.5%, p = 0.005) and coronary artery disease (31.1% vs. 28.0%, p = 0.026). Multivariate regression models demonstrated that psoriasis was not associated with in-hospital case-fatality in patients with ESRD (OR 1.02 (95%CI 0.78-1.33), p = 0.915). Conclusions: ESRD patients with the concomitant psoriasis diagnosis were hospitalized on average 5 years earlier than patients without psoriasis. A higher prevalence of severe life-shortening comorbidities including coronary artery disease and cancer was detected in ESRD patients with psoriasis despite their younger age. Our findings support the understanding of psoriasis as an autoimmune skin disease crossing the boundary between dermatology and internal medicine.
Gesehen am 22.03.2023